EDUCO/United States Forest Service Lonetree - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2002)
Located in: Fort Collins office files. Includes notes; EDUCO call history for December 4, 2002; printouts of email correspondence; and an annotated printout of the Educo Colorado webpage to join the mailing list.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado